FINE TUNING PROBLEM IN FIVE-DIMENSIONAL BRANE WORLD MODELS - Fakhr, S. H.; Eingorn, M.; Zhuk, A. (Одеські астрономічні публікації, 2012)
Fine tuning can be called a main disadvantage of the Randall-Sundrum model, representing the most popular brane world model, constructed quite artificially in the five-dimensional space-time. It needs a bare multidimensional cosmological constant, which is related strictly to four-dimensional tension (the brane physical property). Here we try to avoid this problem of naturalness, introducing a perfect fluid with arbitrary equations of state in both three-dimensional external and onedimensional internal spaces parallel with the cosmological constant. It enables to preserve randomness of parameters of the considered model, which represents the direct generalization of the Randall-Sundrum one. We derive equations for background metric coefficients, determining a wide class of new exact solutions, and discuss uselessness of subsequent development of brane world models in view of their unjustified plurality.